The Revelation of Reason: An Explication of the Divine Judgement of Nations in light of John Rawls’ "A Theory of Justice" - Myers, Christopher (The international journal of religion and spirituality in society, 2015)
An exegesis of the Divine Judgement of Nations in Matthew 25: 31 - 46 in light of John Rawls’ A Theory of Justice inspires individuals to work in political institutions for policies that positively affect the lives of the least-advantaged members of society, and indicates a judgement of political institutions. Jesus gathers the nations (ethnos) and separates the sheep from the goats based upon the their treatment of "the least of my brothers/sisters." The classic interpretation is that the Christian community should support its own missionaries and/or impoverished. It may be a judgement regarding the treatment of Christian missionaries by foreign nations. It was not until the 20th century that more universal interpretations became influential. I highlight a number of exegetical features from New Testament criticism and propose a modified universal interpretation as a judgment of communities as corporate entities. John Rawls’ thought experiment in A Theory of Justice indicates an essential feature of justice as fairness based upon an ideal form of human rationality and universal consensus that explicates the revelation of reason in the apocalyptic parable of the Gospel of Matthew. The exigency of reason requires the following question to be answered. How does any policy positively benefit the least-advantaged members of the global community?